The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.08.23.504803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation in clonal Duckweed lineages (Lemna minorL.) reflects current and historical environmental exposures

Abstract: While some DNA methylation variants are transgenerationally stable in plants, DNA methylation modifications that are specifically induced by environmental exposure are typically transient and subject to resetting in germ lines, limiting the potential for transgenerational epigenetics stress memory. Asexual reproduction circumvents germlines, and may be more conducive to long-term memory and inheritance of epigenetic marks. This, however, has been poorly explored. Taking advantage of the rapid clonal reproducti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…PRJNA883550). The filtered methylation data, epiGBS de novo reference, as well as all phenotypic data we deposited in Zenodo (Van Antro et al, 2022a , 2022b ; DOI 10.5281/Zenodo.5680942 ). All analysis R scripts and the epiGBS pipeline scripts corresponding to the pipeline version used to obtain the methylation data have been made publicly accessible via gitlab: https://gitlab.bioinf.nioo.knaw.nl/MorganeA/script‐for‐l.minor‐paper.git .…”
Section: Data Availability Statementmentioning
confidence: 99%
“…PRJNA883550). The filtered methylation data, epiGBS de novo reference, as well as all phenotypic data we deposited in Zenodo (Van Antro et al, 2022a , 2022b ; DOI 10.5281/Zenodo.5680942 ). All analysis R scripts and the epiGBS pipeline scripts corresponding to the pipeline version used to obtain the methylation data have been made publicly accessible via gitlab: https://gitlab.bioinf.nioo.knaw.nl/MorganeA/script‐for‐l.minor‐paper.git .…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Although not statistically significant after correcting for false discovery rate, patterns of differential methylation in the CHG context (and to a lesser extent in the CHH context) were much more localised than in the CpG context, suggesting this context may have a functional role in S. dumicola. Intriguingly, recent work in plants has suggested that differential methylation in non-CpG contexts may be associated with environmental variation and response to stress (Li et al, 2020;López et al, 2022;Antro et al, 2022). For example, woodland strawberry (Fragaria vesca) show global decrease of 1.8% in CHG methylation in response to salt stress and an increase of 3.1% when challenged with simulated hormone stress, while differential methylation was more common in the CHH context than either of the CpG or CHG contexts (López et al, 2022).…”
Section: Discussionmentioning
confidence: 99%